Human impact on the biosphere basics of ecology - Hildebrandt, Jeff (Colorado Springs, Colo. : Great Pacific Media, 2005)
'Introduces the concept of biological magnification before looking at the various types of air pollution and their relationship to phenomena such as smog, acid rain, destruction of the ozone layer and global warming'
Title from title screen
DVD includes PDF files of a teacher's guide, student study guide, multiple choice test, and a crossword puzzle. Files are accessable by Mac or PC.A sheet of intruction note inserted in container
Video/audio editing : Jennifer Hildebrandt
Narrated by Dan Smith
Keywords: Ecology -- Study and teaching; Biosphere -- Effect of human beings on; Environmental degradation; Environmental impact analysis; Human ecology